Glucagon-like peptide-1, fibroblast growth factor 21, and other endocrine responses to alcohol ingestion in women before and after metabolic surgery - Molina-Castro, Mariel; Rowitz, Blair; Pepino, Marta Yanina (Frontiers in Pharmacology, 2025)
IndroductionGlucagon-like peptide-1 (GLP-1) is integral to glucose homeostasis, appetite, and reward pathways in the brain, making GLP-1 receptor agonists effective treatments for type 2 diabetes, obesity, and potentially alcohol use disorder (AUD). Although metabolic surgery increases endogenous GLP-1, it is paradoxically associated with a higher risk of AUD.MethodsBuilding on cross-sectional research indicating that alcohol consumption decreases endogenous GLP-1 and may contribute to a heightened risk of hypoglycemia post-metabolic surgery, this longitudinal, within-subject study examined whether acute alcohol intake reduced GLP-1 and increased fibroblast growth factor 21 (FGF21)–a liver-derived hormone implicated in glucose regulation and alcohol consumption in animal models –more profoundly after surgery. Seven women were assessed using a randomized, crossover design; they consumed after overnight fast a standardized alcohol-containing beverage or placebo during two separate visits before surgery and repeated these interventions ∼5 months post-surgery. Blood samples were collected over 3 hours to measure blood alcohol concentration (BAC), and plasma glucose, GLP-1, FGF21, insulin, and C-peptide.ResultsPost-surgery, BAC peaked faster and at higher concentrations, and alcohol clearance decreased by ∼28%–likely reflecting the loss of fat-free mass. However, the acute GLP-1 decrease and profound FGF21 increase following alcohol intake were not magnified in the postoperative period, nor did alcohol-induced reductions in glucose become more pronounced.DiscussionThese findings suggest that, despite substantial weight loss and improvements in insulin sensitivity, acute alcohol consumption in the fasted state elicits comparable effects on GLP-1, FGF21, and glycemia before and a few months after metabolic surgery. Further studies with larger and more diverse cohorts are warranted to confirm these observations, clarify long-term effects on alcohol metabolism and glycemic control, and inform strategies to mitigate the potential risk of AUD in this population.Trial RegistrationNCT02766322.